Aqueous phase reforming of glycerol using doped graphenes as metal-free catalysts. Issue 13 (26th May 2017) - Esteve-Adell, Iván; Crapart, Bertrand; Primo, Ana; Serp, Philippe; Garcia, Hermenegildo
Abstract : Boron-doped graphene obtained by pyrolysis at 900 °C of the boric acid ester of alginate was found to be the most active graphene among a series of doped and co-doped graphenes to promote the aqueous phase reforming of glycerol at 250 °C. Abstract : Boron-doped graphene obtained by pyrolysis at 900 °C of the boric acid ester of alginate was found to be the most active graphene among a series of doped and co-doped graphenes to promote the aqueous phase reforming of glycerol at 250 °C. This reaction is of interest in the context of valorization of the aqueous wastes of carbohydrate syrups. Control experiments adding to undoped graphene 1 wt% of triphenylborane, tris(pentafluorophenyl)borane or bis(pinacolyl)diborane as models of possible boron atom types present in B-doped graphene, and boric acid that could be present in a residual amount after pyrolysis, show in all cases an increase in the catalytic activity of graphene. B-doped graphene has also activity for glucose aqueous phase reforming. B-doped graphene undergoes deactivation upon reuse, probably due to B leaching. The results show that graphenes are promising metal-free catalysts for aqueous phase reforming and are alternatives to those containing platinum.